Is Service-Learning the Kind Face of the Neo-Liberal University? - Raddon, Mary-Beth; Harrison, Barbara A. (Canadian Journal of Higher Education, 2015)
The emergence of service-learning pedagogies in Canada has received a variety of critical responses. Some regard service-learning as a public relations effort of universities and colleges; others see it as a countermovement to academic corporatization; still others consider it part of a wider cultural project to produce self-responsible and socially responsible, enterprising citizens. In this article, we argue that each type of response rests on a different critique of the neo-liberal context of post-secondary education; these critiques, in turn, stem from different conceptions of neo-liberalism: as policy, ideology, or governance (Larner, 2000). Rather than attempt to resolve contradictions among these conceptualizations, we address them as a framework for understanding divergent responses to service-learning. We illustrate the framework with the example of a high-enrolment undergraduate course, and we call for future research and educative engagement with the politics of post-secondary service-learning that is informed by a multi-faceted analysis of neo-liberalism.